Monitoring of particle sizes distribution during Valsartan precipitation in the presence of nonionic surfactant - Trunov, Dan; Francisco Wilson, Jose; Ježková, Martina; Šrom, Ondřej; Beranek, Josef; Dammer, Ondřej; Šoóš, Miroslav (International journal of pharmaceutics, 2021)
Particle size is a key parameter when dealing with drug particle formation, delivery or dissolution. The correct measurement of particle size depends on various factors, such as sample preparation or dilution, but also on the choice of method for its characterization. In this work, we study the process of precipitation of poorly water-soluble drug Valsartan from supersaturated solution in the presence of nonionic surfactant Tween 20. Several techniques including dynamic light scattering (DLS) operated in several measuring modes, optical microscope (OM) and static light scattering (SLS) were used to analyze the kinetics of particle formation. As concluded by the results, the increase in turbidity of the solution seriously limits the application of classical DLS to properly measure the particle size and polydispersity. One way to get around this restriction is by dilution, which however results in a decrease in the size of Valsartan particles in the studied population. In contrast, here we present for a first time technique based on modulated 3D cross correlation DLS equipped with the sample goniometer to determine size of submicron particles of the drug in highly turbid solutions. Additionally, a modified OM was used to measure micron-sized particles for samples without any dilution in a continuous mode. Measured particle sizes combined with measured Valsartan concentration allowed us to identify mechanism responsible for the particle formation from supersaturated solutions. The main mechanism, as it is shown in this work, is covering surface of precipitate particles by the amount of used Tween 20.
Keywords: léčivé přípravky; Valsartan; dynamický rozptyl světla; povrchově aktivní látky; velikost částic; Dynamic Light Scattering; valsartan; Pharmaceutical Preparations; Surface-Active Agents; Particle Size